Analisis Kesalahan Mahasiswa Dalam Menyelesaikan Soal Stoikiometri - Kasih Haryo Basuki (Peneliti.net, 2020)
The purpose of this study was to determine the location and description of errors that are often made by students in working on Stoichiometric questions. This type of research is descriptive research. This research uses qualitative and quantitative approaches. The qualitative approach is used when analyzing student answers and the quantitative approach is to count the number of students who make mistakes. The subjects of this study were 32 students in the third semester of the Mathematics Education Study Program at Indraprasta University PGRI Jakarta, class of 2019, who were studying Basic Chemistry courses. The results showed that there was an average of 33.44% of students who were tested, wrong in solving stoichiometric questions, these errors included errors in understanding the concepts used to solve the questions, errors in using data, technical errors in making calculations and errors in drawing conclusions. the final result. Misconceptions include assuming that the chemical reaction that occurs does not follow the law of conservation of mass, assumes the number of particles is equal to the number of moles, assumes the limiting reagent is the reactant with the least number of moles, assumes the number of moles is equal to the mass and assumes the mass of the substance is proportional to the coefficient of the substance.